Analysis of The Role of Car Spareparts Sales Applications as A Digital Transformation Strategy in Four-Wheel Vehicle Service Companies - Fahrudin, Rifqi; Suwandi, Suwandi; Septian, Willy Eka; Putri Hernawan, Ratu Asshyffa; Francisko, Valerio Kenny (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Digital transformation is essential for four-wheel vehicle service companies to enhance competitiveness and operational efficiency. One widely adopted strategy is the use of car spare parts sales applications integrated with workshop services. This study aims to analyze the role of such applications as a digital transformation strategy in four-wheel vehicle service companies. A descriptive qualitative approach was employed through direct observation, in-depth interviews with business owners and operational managers, and documentation analysis. The findings show that the application improves inventory control, accelerates transaction processes, enhances financial record accuracy, and supports better coordination between sales and service activities. However, challenges related to employee adaptation and system integration were identified. The study concludes that car spare parts sales applications play a significant role in supporting digital transformation, and their effective implementation requires strong management support, employee training, and continuous system development to achieve sustainable business performance.